2018
DOI: 10.1063/1.5026691
|View full text |Cite
|
Sign up to set email alerts
|

Formation of H2 on graphene using Eley-Rideal and Langmuir-Hinshelwood processes

Abstract: A hydrogen atom can either physisorb or chemisorb onto a graphene surface. To describe the interaction of H with graphene, we trained the C-C, H-H, and C-H interactions of the ReaxFF CHO bond order potential to reproduce Density Functional Theory (DFT) generated values of graphene cohesive energy and lattice constant, H dissociation energy, H on graphene adsorption potentials, and H formation on graphene using the Eley-Rideal (ER) and Langmuir-Hinshelwood (LH) processes. The results, generated from the trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
4
11
0
Order By: Relevance
“…This is the result of the high stability of the pristine pyrene with respect to its hydrogenated counterparts. The energy barriers for the H 2 formation found on pristine pyrene are slightly higher than what was found previously on graphene; 45,46 this confirms that small graphene-nanoflakes like pyrene behave like graphene when H 2 formation is considered. Fig.…”
Section: Molecular Hydrogen Formationsupporting
confidence: 68%
“…This is the result of the high stability of the pristine pyrene with respect to its hydrogenated counterparts. The energy barriers for the H 2 formation found on pristine pyrene are slightly higher than what was found previously on graphene; 45,46 this confirms that small graphene-nanoflakes like pyrene behave like graphene when H 2 formation is considered. Fig.…”
Section: Molecular Hydrogen Formationsupporting
confidence: 68%
“…A small barrier ("10 meV, or " 115K) may be present, but we chose to neglect it (Casolo et al 2009). Petucci et al (2018) computed a high energy of 1150 K for the barrier. found that the D abstraction on low D-covered graphite bombarded with H-atoms proceeds with a cross-section of up to 17 Å 2 (and 4 Å 2 at high coverage).…”
Section: H 2 and Hd Formation On Neutral And Cationic Pahsmentioning
confidence: 99%
“…In chemical adsorption, a C atom on graphene forms an sp 3 -hybridized orbital, which involves overcoming an energy barrier. Petucci et al [381] studied the interaction between hydrogen and graphene and optimized the potential of the chemisorption of H on graphene. In the results of their sim-ulation of physical adsorption, the positions depicted with darker colors absorb H atoms easily.…”
Section: Theoretical Study Of the Hermentioning
confidence: 99%